Fabrication of monolithic capillary columns with inner diameter 50–530 μm employing a mixture of pentaerythritol tetraacrylate and polyhedral oligomeric silsesquioxane‐methacrylate as crosslinkers. Issue 17 (10th April 2022) - Planeta, Josef; Moravcová, Dana; Karásek, Pavel; Roth, Michal
Abstract : Highly crosslinked monolithic capillary columns with inner diameters in the range of 50–530 μm were prepared by radical polymerization of pentaerythritol tetraacrylate, polyhedral oligomeric silsesquioxane‐methacrylate, and n ‐octadecyl methacrylate in the presence of methanol, dodecyl alcohol, and polyethylene glycol lauryl ether. Columns were evaluated by inverse size‐exclusion chromatography employing a set of polystyrene standards of narrow molecular‐size distribution and by scanning electron microscopy. Chromatographic performance under reversed‐phase conditions was also evaluated. The combination of two effective crosslinkers as pentaerythritol tetraacrylate and polyhedral oligomeric silsesquioxane‐methacrylate in the polymerization mixture allows for the preparation of robust and efficient monolithic capillary columns within a fairly wide range of internal diameters.